A Field Experimental Design of a Strengths-Based Training to Overcome Academic Procrastination: Short- and Long-Term Effect - Visser, Lennart; Schoonenboom, Judith; Korthagen, Fred A. J. (Frontiers in Psychology, 2017)
This study reports on the effect of a newly developed four-week strengths-based training ap-proach to overcome academic procrastination, given to first-year elementary teacher education students (N = 54). The training was based on a strengths-based approach, in which elements of the cognitive behavioral approach were also used. The purpose of the training was to pro-mote awareness of the personal strengths of students who experience academic procrastination regularly and to teach them how to use their personal strengths in situations in which they usually tend to procrastinate. With a pretest-posttest control group design (two experimental groups: n = 31, control group: n = 23), the effect of the training on academic procrastination was studied after 1, 11, and 24 weeks. Results of a one-way analysis of covariance revealed a significant short-term effect of the training. In the long term (after 11 and 24 weeks), the scores for academic procrastination for the intervention groups remained stable, whereas the scores for academic procrastination for the control group decreased to the same level as those of the intervention groups. The findings of this study suggest that a strengths-based approach can be helpful to students at an early stage of their academic studies to initiate their individual process of dealing with academic procrastination. The findings for the long term show the importance of measuring the outcomes of an intervention not only shortly after the interven-tion but also in the long term. Further research is needed to find out how the short-term effect can be maintained in the long-term.